A study of the genus Cyrtosia Perris (Diptera: Mythicomyiidae: Platypyginae) in Yazd province, Iran, with description of a new species - Hakimian, Saeedeh; Nozari, Jamasb; Gharali, Babak; Evenhuis, Neal (Zootaxa, 2018)
The genus Cyrtosia Perris (Mythicomyiidae: Platypyginae) was studied in Yazd province in the center of Iran. Three species were collected and identified. A new species, Cyrtosia trivitta sp. nov., is described and its diagnostic characters are illustrated. This species is clearly different from all described species of Cyrtosia in Iran by presence of three black longitudinal stripes on mesonotum, leaving prescutellar area yellow opposite to the other species that have a large seamless black mark.